Implementasi Kebijakan PBB Perdesaan dan Perkotaan di Provinsi DKI Jakarta - Yusuf Agil Pamungkas; Evi Satispi (Matra Pembaruan: Jurnal Inovasi Kebijakan, 2022)
Regulation Number 28 of 2009 on the Regional Taxes and Levies mandated delegation of Land and building tax-rural and urban (PBB-P2) policy to the Regional Government. However, tax database has a problem, including double determination of one tax object. This study aims to analyze the implementation of PBB-P2 policy in DKI Jakarta Province. This study used descriptive qualitative method. Data collection techniques using documentation, interviews, and observation. According to Edwards III’s theory, the results showed that implementation of PBB-P2 policy in DKI Jakarta Province is influenced by four aspects: communication, resources, disposition, and bureaucratic structure. The leaders have a clarity and consistency for transmitting policy goals to the implementers. Human and financial resources allocated to support PBB-P2 policy are limited, thus hampering tax database validation process. The implementer has integrity, commitment, and responsibility to carry out the policies. The bureaucratic structure clearly illustrates the separation of duties and functions between implementers.